L’Affaire Salman Rushdie: symptôme d'un « Clash of Civilizations »? - Dupuis-Déri, Francis (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
Samuel Huntington proclaimed in an already well-known article ("Clash of Civilizations?") that deep incompatibilities between great civilizations will be the primary cause of future international conflicts. Conflicts will be cultural rather than economic or ideological. To test the validity of this claim, I analyse an international conflict which is truly cultural : the "Salman Rushdie Affair". This affair was provoked by the publication of Rushdie's novel, The Satanic Verses. By studying the motives of the actors in this event (the novelist Salman Rushdie, the imam Ruhollah Musavi Khomeini and the politician Margaret Thatcher), it seems at first sight that they were driven by political or financial interests. But a closer analysis shows that these actors were directed by cultural motivations. Does this prove that Huntington's thesis is right ? No, since even if the actors tried to defend a vision of their culture, there is no such a thing as monolithical civilizations but rather, there are only multicultural civilizations. Indeed, many people from the West refused to defend Rushdie, many Muslims condemned Khomeini's fatwa and Thatcher promoted only one aspect of Western political culture. Values are transnational and an Iranian may cherish the same values as an inhabitant of New York, while, on the other hand two Londonners living in the same flat dream about killing the other over the abortion issue.